Pengaruh Sikap Terhadap Perilaku Ramah Lingkungan (Kasus Sebuah Komunitas di Bantaran Sungai Ciliwung Kota Bogor) - Megafirmawanti Lasinta; Salahuddin Salahuddin; Suriana Suriana (Fakultas Pertanian Universitas Halu Oleo, 2022)
This research is designed quantitatively and aims to analyze the influence of community attitudes on environmentally friendly behavior. The community under study is Pulo Geulis, a residential area on a delta in the middle of the Ciliwung river, Bogor City. The research location was chosen purposively considering its strategic geographical location and its high tourism potential. Data were collected on 100 respondents with a questionnaire research instrument. Sampling was done by cluster method where each RT (Rukun Tetangga) in Pulo Geulis was represented by 20 respondents. Data analysis was performed using Partial Least Square (PLS) software. The results prove this research hypothesis, that there is a positive and significant effect of community attitudes on environmentally friendly behavior. This is evidenced by the value of T statistic which is greater than T Table (1.96), and the value of P Values which is smaller than 0.05.